THE CIVIC SELF-CONSCIOUSNESS OF CONTEMPORARY SECONDARY SCHOOL STUDENTS IN THE ASPECT OF THE HUMANISTIC PARADIGM OF EDUCATION - Alijevs, Roman; Chehlova, Zoja; Kevisa, Ingrida; Chehlovs, Mihail (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
Civic self-consciousness is a topical issue in present-day Latvia. After regaining of independence and joining the European Union, there appeared an opportunity to ensure real freedom and genuine democracy for all inhabitants in Latvia. Thus, new conditions were created for the development of civic self-consciousness in senior secondary school students. New guidelines are developed in the European system of education according to the new understanding of humanism.  The key reference-point is the understanding that the main goal of education is to support the development of personality that will become an EU citizen and a professional. The study established that it is necessary to develop civic self-consciousness so that Latvian secondary school students could become European-type citizens and professionals.The research deals with the analysis of a new model of education, the basis for developing civic self-consciousness in senior secondary school students. The research has determined the structure of civic self-consciousness and demonstrated the interconnectedness of its structural components (tolerance, responsibility and intercultural identity). The aim of the research: to analyse the possibilities of a new model of education in developing the civic self-consciousness of senior secondary school students, to determine its essence, structure and characteristics. The research methods include analysis, survey, testing, conversation, an ascertaining experiment, mathematical statistics. The research results: there was determined the structure of civic self-consciousness as a precondition for the development of civic self-consciousness in senior secondary school students and conducted the analysis of ideas concerning new humanism in education and a new model of education (education – culture – individual).